APLIKASI CITRA LANDSAT 8 MULTITEMPORAL UNTUK MONITORING KERUSAKAN TERUMBU KARANG DI PULAU SETAN KEC. XI KOTO TARUSAN KAB. PESISIR SELATAN TAHUN 2013-2019 - Rafiqah Indah Sari; febriandi febriandi (JURNAL BUANA, 2020)
Coral reefs in the waters of West Sumatra are under threat. From a total of 21,486,989 hectares, it decreased by 75% or 16115.23 hectares in 2017. The aim of the researchers was to obtain changes in the area of ​​coral reefs from 2013, 2016 and 2019 in Pulau Setan, Kec. XI koto Tarusan Kab. Pesisir Selatan, knowing what are the causes of damage and changes in the location of coral reefs and finally knowing what should be done by the government and society. The research method used in this research is descriptive qualitative. The data analysis technique used lyzenga analysis to find out how the distribution of coral reefs. The results showed that, 1 From the results of Lyzenga, it was found that in Satan Island, changes in the area of ​​coral reefs had decreased in area of ​​75561.996 m2 in a period of 6 years. 2 Some of the factors that cause the reduction and displacement of coral reefs are temperature and brightness, where the temperature is above normal limits, and brightness is limited to normal. Corals can move places due to sea waves. 3 There are several efforts that have been made by the community and government in terms of coral reef conservation. The first activity was carried out by the Marine Lantamal II Padang Battalion and the UBH Diving Proclaimer. The second activity was carried out by Suparno, Abdullah Munzir, and Kamila Suryani.